The relationship between human investment and economic growth in Iraq(1985-2010) and measuring return of investment of human - عيسى رجاء عبد الله (Journal of Economics and Administrative Sciences, 2013)
Abstract: Investment in human capital of renewable energy can be relied upon to get to achieve the goals of development is important for Iraq through the intellectual community cards creative able to innovate and develop what is so is study the effect of human investment on economic growth through the adoption of the index of national income as a function of variables independent ( human capital, physical capital) and this is built on the premise that the relationship direct correlation between economic growth and human investment, and it can measure the return on human investment, which is an incentive to increase human capital through education and the development of the economy in general have shown the study hypothesis above by adopting the method of Econometrics, as well as decreasing the rate of return for investment of the human for the duration (1985-2010), and this is reflected in the low productivity of the individual and the society as he represents a good incentive for the low human capital and the reluctance of education, study and engage in the work of non-productive that does not require the head of human art.